2018
DOI: 10.3389/fenvs.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Aerosol Over Ukraine Region: Current Status of Knowledge and Research Efforts

Abstract: In this paper the current status of knowledge and research efforts on atmospheric aerosol investigation over Ukraine region are reviewed. Several earlier results of atmospheric extinction, aerosol content and properties studies performed in Ukraine during the second part of the twentieth century are discussed. The recent findings on aerosol optical depth, Ångström exponent, optical and microphysical properties of aerosol particles (single-scattering albedo, size distribution, complex refractive index) and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…In the present study, we considered daily averages of AOD at 500 nm, Ångström exponent (AE) values computed using the 440-870 nm spectral channels, particles columnar size distribution, single-scattering albedo (SSA), and complex refractive index (RI). Analysis of the previous observations showed that typical AOD values at wavelengths 500 nm at the Kyiv site do not exceed 0.2-0.3 [6,33,50].…”
Section: Aeronet Sun-photometer Datamentioning
confidence: 90%
See 1 more Smart Citation
“…In the present study, we considered daily averages of AOD at 500 nm, Ångström exponent (AE) values computed using the 440-870 nm spectral channels, particles columnar size distribution, single-scattering albedo (SSA), and complex refractive index (RI). Analysis of the previous observations showed that typical AOD values at wavelengths 500 nm at the Kyiv site do not exceed 0.2-0.3 [6,33,50].…”
Section: Aeronet Sun-photometer Datamentioning
confidence: 90%
“…The AERONET data are useful to study the local aerosol behavior and seasonal dynamics. For the purposes of the paper, we used the data of the Kyiv AERONET site, which has continuously operated by authors since 2008 in the southwest part of the city of Kyiv [33,50,51]. The Kyiv AERONET site is located on the roof of the building where the Golosiiv Air Visual sensor is installed (see Figure 1, station 2) [51].…”
Section: Aeronet Sun-photometer Datamentioning
confidence: 99%
“…For example, Saharan desert dust was detected over the southeastern United States [8]. The results of the detection of mineral dust in Northern, Southern and Eastern Europe can be found in [9][10][11][12]. The contamination of the Cyprus atmosphere by Saharan dust outbreaks over Nicosia was studied by Amiridis et al [13], and Papayannis et al [14].…”
Section: Introductionmentioning
confidence: 98%